Surprisingly Sarah - Libenson, Terri (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2023)
"Sarah and Leo have been best friends since they were little. They share everything . . . until Sarah starts crushing on Leo's friend Ben. Then one day Sarah is suddenly faced with a big choice: ask Ben to the school dance or chicken out. Either way, Sarah and Leo's friendship will be put to the test"--Provided by publisher.
3-6
3-6
English.
Keywords: Friendship -- Juvenile fiction; Girls -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Fiction; Girls -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Friendship -- Fiction; Girls -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction; School stories; Illustrated works; School fiction